Effects of In Vivo Exposure to Roundup® on Immune System of Caiman latirostris. - Latorre, María Agustina (2013)
The present study aimed to evaluate the effect of Roundup® (RU, glyphosate-based formulation) on some parameters of the immune system and growth of Caiman latirostris. Seventy-two caimans (20-day-old) from Proyecto Yacaré (Gob. Santa Fe/MUPCN) were used. Two groups were exposed for 2 months to different concentrations of RU (11 or 21 mg/L; taking into account the concentration recommended for its application in the field), while one group was maintained as control. The RU concentration was progressively decreased through the exposure period to simulate glyphosate degradation in water. Animals were measured and weighed at the beginning and end of the experiment, and blood samples taken after exposure to determine total and differential white blood cell (WBC) counts as well as total protein concentration (TPC), and for performing protein electrophoresis. The results showed that, compared against control hosts, there was a decrease in WBC counts, a higher percentage of heterophils, a higher TPC (with a low percentage of F2 protein fraction), and a negative effect on growth in the young caimans exposed to RU. These results demonstrate that in vivo exposure to RU induced alterations in the selected immune parameters, plasma proteins, and growth of caimans, thereby providing relevant information about the effects of this type of pesticide in this important species in the Argentinian wetlands.